National MPC policies of cooperation with the EU in Science and Innovation: the case of Morocco - El Fellah R.; El Majid Z. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
The EU and Morocco are fully engaged in a strong and deep cooperation supported by a high-level policy dialogue, and pertaining to multiple sectors including research and innovation. At the institutional level, the Association agreement (1996), the ST agreement (2003), the European neighbouring policy (2004), the new ‘advanced status’ and the programme called “To succeed the advanced status” have put emphasis on the consolidation of scientific and technological ties, and are supported by relevant implementation mechanisms and instruments. In May 2011 an institutional twinning program was launched to strengthen and bring closer the Moroccan research and innovation system to ERA. Morocco is highly devoted to reinforce and intensify the current bilateral initiatives and programmes in the field of science and technology, aiming to the preparation and definition of joint activities targeting themes of mutual interest, the improvement of cooperation on industry-oriented ST cooperation between EU and Morocco, the setting up of joint collaboration and networking of technical platforms and research laboratories. Through these efforts, the scientific and technological cooperation with the EU is considered as a driver for the implementation of the national strategy for research Horizon 2025, a support to sectoral national programmes of socio-economic development and to the achievement of the knowledge-based economy.